2015
DOI: 10.1007/s10549-015-3305-7
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 is a highly significant prognostic marker of hormone-receptor-positive, human epidermal growth factor receptor-2-negative breast cancer

Abstract: B-cell lymphoma-2 (Bcl-2) is one of the most important anti-apoptotic genes. Although Bcl-2 promotes tumor cell survival in vitro, previous studies have shown conflicting results regarding the association between Bcl-2 and breast cancer survival. The aim of this study was to assess the prognostic significance of Bcl-2 according to the molecular tumor subtype in primary invasive breast cancer patients. The relationship between immunohistochemical Bcl-2 expression and overall survival was analyzed in 2399 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
10
19
0
Order By: Relevance
“…The present study reveals high expression levels of Bcl-2 in the luminal A and luminal B subtypes of breast cancer in comparison with that in the HER2 + and triple-negative molecular subtypes. These results are concordant with those from Seong et al (53), which also described a significant association between Bcl-2-positive tumors, and a younger patient age, early stage, lower grade, positive expression of ER and PR, and negative expression of HER2. Patients with Bcl-2/ER/PR-positive and HER2-negative tumors in this previous study also exhibited an improved prognosis (53).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study reveals high expression levels of Bcl-2 in the luminal A and luminal B subtypes of breast cancer in comparison with that in the HER2 + and triple-negative molecular subtypes. These results are concordant with those from Seong et al (53), which also described a significant association between Bcl-2-positive tumors, and a younger patient age, early stage, lower grade, positive expression of ER and PR, and negative expression of HER2. Patients with Bcl-2/ER/PR-positive and HER2-negative tumors in this previous study also exhibited an improved prognosis (53).…”
Section: Discussionsupporting
confidence: 92%
“…These results are concordant with those from Seong et al (53), which also described a significant association between Bcl-2-positive tumors, and a younger patient age, early stage, lower grade, positive expression of ER and PR, and negative expression of HER2. Patients with Bcl-2/ER/PR-positive and HER2-negative tumors in this previous study also exhibited an improved prognosis (53). A significant correlation between Bcl-2 expression levels and hormone receptor status demonstrates that Bcl-2 is a potential effective marker of hormonal responsiveness in patients with ER/PR positive breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Although they reported that BCL2 was a favorable prognostic factor regardless of ER, PR, and HER2, BCL2 was not analyzed according to the combination of HR(+) and HER2(−). Seong et al [24] reported that BCL2 expression was an independent, favorable prognostic factor only in breast cancer patients with the HR(+)/HER2(−) subtype and that BCL2 was not a significant prognostic factor in the other subtypes, including HR(+)/HER2(+), HR(−)/HER2(+), and HR(−)/HER2(−) subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demographic and basic clinical information, an increasing number of novel prognostic markers have been explored and identified 10 12 . However, the main problem for most of these studies is that biomarkers rely on sophisticated molecular and/or genetic tests 11 , 13 16 . The practical application of the novel tests is inevitably restricted by its cost and complexity.…”
Section: Discussionmentioning
confidence: 99%